Impact of social fairness perception on sense of social security in China’s COVID-19 pandemic: the mediating role of political trust - Wang, Jianwen; Zhang, Jingwen (Frontiers in Psychology, 2025)
IntroductionAgainst the backdrop of the COVID-19 pandemic, emerging threats previously obscured were revealed and instilled a profound sense of insecurity across the globe. The exacerbation of unequal access to essential resources during the pandemic, particularly in rural-urban divides (e.g., healthcare infrastructure, economic relief distribution), has objectively contributed to a decline in individuals’ perceptions of social security, with rural residents facing compounded vulnerabilities. Thus, an exploration of the interplay between the variables of social fairness perception and sense of social security is warranted to provide empirical evidence and guidance for improved social governance and policy formulation in response to future social challenges.MethodsThis study, grounded in the data sourced from the 2021 China Social Survey (CSS 2021), utilizes the ordinal multivariate regression model within SPSS to conduct an in-depth exploration of the intrinsic relationship between social fairness and residents’ perceptions of social security. Results: Through the application of hierarchical multivariate stepwise regression analysis, the study reveals that both opportunity fairness (β = 0.41, p < 0.001) and outcome fairness (β = 0.43, p < 0.001) significantly predicted heightened perceptions of social security. These effects remained robust after controlling for demographic variables (e.g., age, residence) and contextual factors (e.g., living environment, social welfare). Mediation analysis using bootstrapping (5,000 resamples, bias-corrected) revealed that political trust partially mediated the relationship between fairness perceptions and social security. Specifically, political trust accounted for 20.7% of the total effect of opportunity fairness (indirect effect: β = 0.10, 95% CI [0.06, 0.15]) and 27.8% of the effect of outcome fairness (indirect effect: β = 0.12, 95% CI [0.08, 0.17]). Moderated mediation analysis further indicated urban-rural disparities: urban residents exhibited significantly stronger mediation through outcome fairness (β = 0.15) compared to rural counterparts (β = 0.11).DiscussionThe findings extend institutional trust theory by demonstrating that procedural equity (e.g., transparent policy implementation) reinforces governance legitimacy during crises. To mitigate disparities, policymakers should standardize urban-rural welfare systems to address unequal mediation pathways and institutionalize participatory equity audits in crisis governance frameworks. These measures operationalize the critical link between fairness perceptions and societal resilience.